Bayesian Inference of a Uniform Distribution - Minka, Tom (2001)
This note derives the posterior, the evidence, and the predictive density for a uniform distribution, given a conjugate parameter prior. These provide various Bayesian answers to the ``taxicab'' problem: viewing a city from the train, you see a taxi numbered X. Assuming taxicabs are consecutively numbered, how many taxicabs are in the city?